Competency-Based Medical Education: An Analysis of Implementation Challenges in Resource-Limited Settings: Competency Based Medical Education - Abdullah, Zainab; Ayub, Hassan; Saleem, Saiqa; Jabeen, Nadia; Gul, Naveed; Aman, Khaliq (Pakistan Journal of Health Sciences, 2025)
Competency-Based Medical Education (CBME) employs a systematic outcome-based strategy to enhance the practical and clinical competencies of the graduates. CBME faces challenges particularly in low-resource areas due to differences in faculty and institutional support, as well as institutional and learning resource availability. Objective: To determine the conditions that affect CBME readiness among academic staff and to determine what may obstruct its effective execution. Methods: A cross-sectional study was completed over 6 years (September 2024 - January 2025) with a total of 110 faculty members. The participants were divided into 2 groups using a validated assessment tool aimed at targeted differences in CBME readiness. Subjects filled out questionnaires which were analyzed through chi-squar and independent t-tests. Results: The factors affecting readiness towards CBME age, faculty experience, and student-patient ratios were not significant. Access to digital resources, government funding, and institutional support were significantly associated with higher levels of readiness. Faculty who participated in the simulation-based training and the competency evaluation showed higher levels of readiness for CBME. The training of faculty members did not impact the level of readiness to any significant degree, which points to the necessity of continuous mentoring and practical work. Conclusions: For the adoption of CBME, institutional support, the presence of digital tools, and access to competency-based evaluations are essential. All three of these factors can enhance faculty’s willingness to participate and subsequently improve the effectiveness of medical education. Investing in structured faculty training and technological resources will help a smoother transition to CBME